Access and utilization of the youth-friendly sexual and reproductive health services in Nepal: What does literature show? - Adhikari, Bhabani; Adhikari, Ramesh (Journal of Health Promotion, 2021)
This study has attempted to assess the access and utilization of youth-friendly sexual and reproductive health services in Nepal. Different literature regarding youth-friendly sexual and reproductive health services has been reviewed using online databases. A total of 125 relevant articles were assessed for the study. The literature was categorized and analyzed with five key thematic areas: knowledge on SRH among youths, the prevalence of child marriage and teenage pregnancy, attitudes towards premarital sex, utilization of SRHs, and barriers to utilizing the SRHS. This study has found that youths do not always utilize SRHS. Various barriers exist for providing and using YFSRHs in Nepal. Nepal's adolescents and youths face problems of STIs, HIV/AIDS, early pregnancy and parenthood, difficulties accessing contraception, and safe abortion. The study has also found that many countries have single youth-friendly sexual and reproductive health policies and that utilization of SRHS is also high in those countries. Moreover, this review has also found that because of inadequate knowledge and information on SRHS, Nepalese youths are facing numerous reproductive health problems. Multiple factors contribute as barriers to utilizing the SRHS. Therefore, there is a need for a program to motivate youths to respect their right to access reproductive health information and service, ensure the availability of peer counselors in the health centers, and increase the awareness level of the community so that they can utilize the quality of SRHS.